Detecção de anticorpos anti-Leishmania spp. em aves domésticas de Santa Maria-RS, sul do Brasil - Tatto, Maurício (2023)
Domestic birds such as chickens (Gallus gallus), turkeys (Meleagris gallopavo) and geese (Anser anser) are raised extensively, coexisting with humans, domestic and wild animals, known to be hosts and reservoirs of protozoa of the genus Leishmania. In addition, the blood of these birds is a preferred source of food for insect vectors of the Phlebotominae family, suggesting that they may act as bioindicators of the circulation of these protozoans (SANT'ANNA ET AL. 2010). Therefore, this study aimed to investigate the presence of antiLeishmania spp. antibodies in poultry in the rural area of the municipality of Santa Maria, southern Brazil, using the Indirect Immunofluorescence Reaction (IFAT). Between May and December 2022, 262 blood samples were collected from (244/262 - 93%) chickens (Gallus gallus), eight (8/262 - 3%) turkeys (Meleagris gallopavo), seven (7/262 - 3%) guinea fowl (Numida meleagris) and three (3/262 - 1%) geese (Anser anser), distributed in 27 rural properties in six districts of the municipality of Santa Maria, Rio Grande do Sul, Brazil. All locations visited had reactive birds for anti-Leishmania spp. antibody titers. Of the 244 blood samples collected from chickens (Gallus gallus), 181 samples (74%) were reactive for 30 antibody titers, as well as six (75%) turkeys (Meleagris gallopavo) and three (100%) geese (Anser anser), while none of the guinea fowl showed serological reactivity. Thus, it is possible to infer that although birds have physiological mechanisms that make them immune to infection by Leishmania spp., contact with these protozoa may be able to induce the production of antibodies in these animals, making them possible bioindicators in leishmaniasis, of the presence of both both vectors and protozoa.